Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

Microbial consortium effects on plant–microbe interactions, wheat productivity, and soil fertility - Gowardhan Kumar Chouhan; Arpan Mukherjee; Pankaj Trivedi; Arthur Prudêncio de Araujo Pereira; Anand Kumar Gaurav; Tushar Goyal; Bansh Narayan Singh; Jay Prakash Verma (Applied Soil Ecology, 2026)

Retraction notice to “Organic wastes bioremediation and its changing prospects” [Sci. Total Environ. 824 (2022) 153889] - Anil Kumar Patel; Reeta Rani Singhania; Frank Paolo Jay B. Albarico; Ashok Pandey; Chiu-Wen Chen; Cheng-Di Dong (Science of The Total Environment, 2026)

Field application of functionalized carbon nanotubes improves wheat yield without residue translocation - Shiv Shankar Gautam; G. P. Satsangi; Neelesh Kumar Pandey; Neeraj Kumar Biswas; Sudesh Kumar; Jay Singh (Vegetos, 2026)

Green corrosion inhibition of mild steel in acidic media: electrochemical behavior and theoretical studies of Zingiber mioga essential oil - Lalrin Tluangi; Raj Kumar Mishra; Jay Prakash Rajan; Manisha Malviya; Raghvendu Pathak; Ashish Kumar Singh; Rashmi Sehrawat; Dinesh Kumar Sharma; Sunil Kumar Pandey; Bindu Mangla; Ved Prakash Singh (Environmental Science and Pollution Research, 2026)

Paddy cultivar diversification for management of soil methane emissions and sustainable rice production - Jay Shankar Singh; Shashank Tiwari; Prateek Singh; Rahul Kumar Nigam; Irina K. Kravchenko (Environmental Sustainability, 2025)

Effects of 700 MHz radiofrequency radiation (5 G lower band) on the reproductive parameters of female Wistar rats - Neha Jha; Priyanka Sarsaiya; Anuj Kumar Tomar; Sonali Pardhiya; Jay Prakash Nirala; P.K. Chaturvedi; Surabhi Gupta; Paulraj Rajamani (Reproductive Toxicology, 2025)

A critical review on occurrence, speciation, mobilization, and toxicity of per- and polyfluoroalkyl substances in the soil-microbe-plant system and bioremediation strategies - Lalit Goswami; Pritam Kumar Dikshit; Aman Prakash; Poorna Weerarathna Vidanage; Jay Prakash Verma; Seungdae Oh (Journal of Hazardous Materials, 2025)

Pseudomonas gessardii suppresses Xanthomonas vesicatoria through 4-Dodecylbenzene sulfonic acid interference with virulence proteins - Riddha Dey; Seema Devi; Jay Kishor Prasad; Jatin Jangra; Rajnish Kumar; Richa Raghuwanshi (World Journal of Microbiology and Biotechnology, 2025)

Development of a Novel Sea Ice Drift Detection Algorithm (SIDDA) Using SAR Data - Purvee Joshi; Jay Das; Madhukar Srigyan; Shailendra Saini; Sushil Kumar Singh; Shital Shukla; Sandip Oza (Journal of the Indian Society of Remote Sensing, 2025)

Perfluoroalkyl substances (PFAS) exposure and preeclampsia risk: Impaired angiogenesis through suppression of VEGF signaling - Jay S. Mishra; Bradley Bosse; Kara K. Hoppe; Kristen Malecki; Scott J. Hetzel; Sathish Kumar (Reproductive Toxicology, 2025)

Nanotechnology Driven Lipid and Metalloid Based Formulations Targeting Blood–Brain Barrier (3B) for Brain Tumor - Amulya Jindal; Mainuddin; Anoop Kumar; Ratneshwar Kumar Ratnesh; Jay Singh (Indian Journal of Microbiology, 2025)

A Comprehensive Review on Plant-Based Medications and Chemical Approaches for Autism Spectrum Disorders (ASDs) Psychopharmacotherapy - Vrish Dhwaj Ashwlayan; Ratneshwar Kumar Ratnesh; Divya Sharma; Alok Sharma; Akansha Sangal; Alimuddin Saifi; Jay Singh (Indian Journal of Microbiology, 2025)

Synthesis, In-Silico Molecular Docking Studies, and In-Vitro Antimicrobial Evaluation of Isatin Scaffolds bearing 1, 2, 3-Triazoles using Click Chemistry - Ritesh Anand; Nisha Yadav; Deeksha Mudgal; Simran Jindal; Sunak Sengupta; Deepak Kumar; Jay Singh; Nagendra Kumar Panday; Vivek Mishra (Indian Journal of Microbiology, 2025)

A multizonal numerical combustion model of ammonium perchlorate - Neeraj Kumar Pradhan; Jay Patel; Arindrajit Chowdhury; Debasis Chakraborty; Neeraj Kumbhakarna (Fuel, 2025)

Molecular and serological screening of coxiellosis in bovines with reproductive disorders in dairy farms - Neha Parmar; Satyaveer Singh Malik; Manesh Kumar; Jay Prakash Yadav; V.K. Vinod; M.S. Sivaprasad; Brijesh Kumar; Jess Vergis; E.S. Sanjumon; Sukhadeo Baliram Barbuddhe; Deepak Bhiwa Rawool (The Veterinary Journal, 2024)

Identification and pathogenicity of mycoflora associated with leaf spot disease of Aloe vera - Divya Singh; V. P. Chaudhary; S. K. Singh; Shivam Singh; Jay Kumar Yadav; Harshita (Vegetos, 2024)

Multi-path long-term vessel trajectories forecasting with probabilistic feature fusion for problem shifting - Gabriel Spadon; Jay Kumar; Derek Eden; Josh van Berkel; Tom Foster; Amilcar Soares; Ronan Fablet; Stan Matwin; Ronald Pelot (Ocean Engineering, 2024)

Phytochemical composition, antioxidant and antibacterial properties of methanol stem and leaf extracts of Croton bonplandianus Baill - Indrajeet Kumar; Umesh Kumar; Prince Kumar Singh; Jay Shankar Yadav; Akanksha Dwivedi; Priyanka Singh; Ashutosh Tripathi; Rajesh Kumar Sharma (Vegetos, 2024)

Comparative assessment of anti-ulcer effects: Hydro-ethanolic extract from air-dried ray and disc florets vs essential oil of traditional Tagetes erecta (Asteraceae) in Swiss Albino rats - Amrish Kumar; Vrish Dhwaj Ashwlayan; Ratneshwar Kumar Ratnesh; Jay Singh; Mansi Verma (South African Journal of Botany, 2024)

Extraction of tracer elements of particulate matter emission source using association rule mining - Jay Singh Rajput; Manoj Kumar Trivedi (Atmospheric Pollution Research, 2024)

Analyzing spatio-temporal variability of aquatic productive components in Northern Bay of Bengal using advanced machine learning models - Jay Karmakar; Ismail Mondal; SK Ariful Hossain; Felix Jose; Subbarao Pichuka; Debaleena Ghosh; Tarun Kumar De; Quang-Oai Lu; Ismail Elkhrachy; Nguyet-Minh Nguyen (Ocean & Coastal Management, 2024)

Effect of Biofabricated Silver nanoparticles on Growth parameters in Fenugreek (Trigonella foenum-graecum) - Garvita Singh; Anshul Sheokand; Ashi Gupta; Himani Gupta; Jay Kumar; Renu Soni; Varsha K. Singh; Rajeshwar P. Sinha (Vegetos, 2024)

Fabrication of dual S-scheme based CuWO4/NiFe/WO3 heterojunction for visible-light-induced degradation and reduction applications - Rohit Sharma; Nasarul Islam; Aashish Priye; Deepak Kumar; Jay Singh; Manish Kumar; Prem P. Sharma; Vinay Chauhan; Pooja Shandilya (Journal of Environmental Chemical Engineering, 2024)

Detection of internal crack growth in polyethylene pipe using guided wave ultrasonic testing - Jay Kumar Shah; Hao Wang; Said El-Hawwat (Earthquake Engineering and Engineering Vibration, 2024)

Screening of mustard cultivars for phytoremediation of heavy metals contamination in wastewater irrigated soil systems - Prince Kumar Singh; Jay Shankar Yadav; Indrajeet Kumar; Umesh Kumar; Rajesh Kumar Sharma (Environmental Monitoring and Assessment, 2024)

Seasonal drought severity identification using a modified multivariate index: a case study of Indo-Gangetic Plains in India - Vaibhav Kumar; Hone-Jay Chu (Journal of Hydrology, 2024)

Assessing intra and interannual variability of water quality in the Sundarban mangrove dominated estuarine ecosystem using remote sensing and hybrid machine learning models - Ismail Mondal; SK Ariful Hossain; Sujit Kumar Roy; Jay Karmakar; Felix Jose; Tarun Kumar De; Trinh Trong Nguyen; Ismail Elkhrachy; Nguyet-Minh Nguyen (Journal of Cleaner Production, 2024)

Impacts of Sea Surface Temperature Variability in the Indian Ocean on Drought Conditions over India during ENSO and IOD Events - Vaibhav Kumar; Hone-Jay Chu; Abhishek Anand (Journal of Marine Science and Engineering, 2024)
The characteristics of terrestrial droughts are closely linked to simultaneous fluctuations in climatic factors, notably influenced by sea surface temperature (SST). This study explores the response of vegetation photosynthesis, indicated by solar-induced chlorophyll fluorescence (SIF), in India during the summer monsoon period (JJAS) under drought conditions. Notably, statistically significant associations between SST variations in the tropical Indian Ocean and land-based drought responses (precipitation, temperature, soil moisture, and SIF) were observed, which were attributed to atmospheric teleconnections. The positive phases of El Niño and the Indian Ocean Dipole (IOD) significantly impacted SST, triggering severe droughts in India in 2009 and 2015. The results revealed that positive SST anomalies weaken monsoon flow during the onset period, reducing moisture transmission to the Indian subcontinent. In 2009, the precipitation anomaly showed severe drought conditions (

Spatiotemporal consistency and inconsistency of meteorological and agricultural drought identification: A case study of India - Vaibhav Kumar; Hone-Jay Chu (Remote Sensing Applications: Society and Environment, 2024)

Impaired Removal of the Damaged Mitochondria in the Metabolic Memory Phenomenon Associated with Continued Progression of Diabetic Retinopathy - Renu A. Kowluru; Ghulam Mohammad; Jay Kumar (Molecular Neurobiology, 2024)
Retinopathy fails to halt even after diabetic patients in poor glycemic control try to institute tight glycemic control, suggesting a “metabolic memory” phenomenon, and the experimental models have demonstrated that mitochondria continue to be damaged/dysfunctional, fueling into the vicious cycle of free radicals. Our aim was to investigate the role of removal of the damaged mitochondria in the metabolic memory. Using human retinal endothelial cells (HRECs), incubated in 20 mM D-glucose for 4 days, followed by 5 mM D-glucose for 4 additional days, mitochondrial turnover, formation of mitophagosome, and mitophagy flux were evaluated. Mitophagy was confirmed in a rat model of metabolic memory where the rats were kept in poor glycemic control (blood glucose ~ 400 mg/dl) for 3 months soon after induction of streptozotocin-induced diabetes, followed by 3 additional months of good control (BG < 150 mg/dl). Reversal of high glucose by normal glucose had no effect on mitochondrial turnover and mitophagosome formation, and mitophagy flux remained compromised. Similarly, 3 months of good glycemic control in rats, which had followed 3 months of poor glycemic control, had no effect on mitophagy flux. Thus, poor turnover/removal of the damaged mitochondria, initiated during poor glycemic control, does not benefit from the termination of hyperglycemic insult, and the damaged mitochondria continue to produce free radicals, suggesting the importance of mitophagy in the metabolic memory phenomenon associated with the continued progression of diabetic retinopathy.

Genic-SSR-based genetic diversity and population structure analysis in a global germplasm collection highlights the African origin of winged bean (Psophocarpus tetragonolobus L.) - Kishor U. Tribhuvan; Twinkle Mishra; Sampatirao Dilip; Avinash Pandey; Sudhir Kumar; Jay Lal Mahato; Hanuman Lal Raiger; A. Pattanayak; Binay K. Singh (Genetic Resources and Crop Evolution, 2024)

Development of ionic liquid-capped carbon dots derived from Tecoma stans (L.) Juss. ex Kunth: Combatting bacterial pathogens in diabetic foot ulcer pus swabs, targeting both standard and multi-drug resistant strains - Nisha Yadav; Deeksha Mudgal; Shivakant Mishra; Hitesh Sehrawat; Niraj Kumar Singh; Kalicharan Sharma; Prabodh Chander Sharma; Jay Singh; Vivek Mishra (South African Journal of Botany, 2023)

Evaluation of Aloe vera genotypes against leaf rot disease under field condition - Susheel Kumar; S. K. Pande; S. K. Singh; Jay Kumar Yadav; Rajesh Saini (Indian Phytopathology, 2023)
Aloe vera ( Aloe barbadensis ) is a perennial, succulent plant belongs to the family Liliaceae. Aloe vera leaf rot is one of the major limiting factors in Aloe vera production, which decreases leaf, gel quantity and quality significantly. The experiment was conducted to evaluate the genotypes of Aloe vera against leaf rot disease Out of 26 genotypes, none of genotypes was found the free from disease, three genotypes viz, IC-111280, IC-112531 and IC-112513 were highly resistant, four genotypes viz., IC-111279,IC-112518, IC-285626 and IC-283655 were resistant, nine genotypes viz, IC-310618, IC-471886, IC-310904, IC-112569, IC-112519, IC-112532, IC-310611, IC-310617 and IC-310596 were moderately resistant and rest of the genotype were moderately susceptible to highly susceptible against the disease.

Identifying Size-Segregated Particulate Matter (PM2.5, PM10 and SPM) Sources in an Industrial Town of India - Akhilesh Kumar Yadav; Sunil Kumar Sahoo; Aerattukkara Vinod Kumar; Saba Shirin; Aarif Jamal; Aditi Chakrabarty Patra; Jay Singh Dubey; Virender Kumar Thakur; Pradyumna Lenka; Sarjan Singh; Vivekanand Jha; Raj Mangal Tripathi (Aerosol Science and Engineering, 2023)

Multifunctional Cu:ZnS quantum dots for degradation of Amoxicillin and Dye Sulphon Fast Black-F and efficient determination of urea for assessing environmental aspects - Jyoti Patel; Kshitij RB Singh; Akhilesh Kumar Singh; Jay Singh; Ajaya K. Singh (Environmental Research, 2023)

Advancement in precision diagnosis and therapeutic for triple-negative breast cancer: Harnessing diagnostic potential of CRISPR-cas & engineered CAR T-cells mediated therapeutics - Vinayak Nayak; Sushmita Patra; Kshitij RB Singh; Bristy Ganguly; Das Nishant Kumar; Deepak Panda; Ganesh Kumar Maurya; Jay Singh; Sanatan Majhi; Rohit Sharma; Shyam S. Pandey; Ravindra Pratap Singh; et al. (Environmental Research, 2023)

Voltammetric determination of inorganic arsenic in mildly acidified (pH 4.7) groundwaters from Mexico and India - Martijn Eikelboom; Yaxuan Wang; Gemma Portlock; Arthur Gourain; Joseph Gardner; Jay Bullen; Paul Lewtas; Matthieu Carriere; Alexandra Alvarez; Arun Kumar; Shane O'Prey; Tamás Tölgyes; et al. (Analytica Chimica Acta, 2023)

Perfluorooctane sulfonic acid modulates expression of placental steroidogenesis-associated genes and hormone levels in pregnant rats - Sri Vidya Dangudubiyyam; Jay S. Mishra; Sathish Kumar (Reproductive Toxicology, 2023)

Experimental and numerical investigation of novel lightweight concrete panels made with aerogel and phase change materials - Dileep Kumar; Morshed Alam; Jay Sanjayan (Energy and Buildings, 2023)

Acute radiofrequency electromagnetic radiation exposure impairs neurogenesis and causes neuronal DNA damage in the young rat brain - Kumari Vandana Singh; Chandra Prakash; Jay Prakash Nirala; Ranjan Kumar Nanda; Paulraj Rajamani (NeuroToxicology, 2023)

Spatio-temporal variation of C-PM2.5 (composition based PM2.5) sources using PMF*PMF (double-PMF) and single-combined PMF technique on real-time non-refractory, BC and elemental measurements during post-monsoon and winter at two sites in Delhi, India - Ashutosh Kumar Shukla; Sachchida Nand Tripathi; Francesco Canonaco; Vipul Lalchandani; Ravi Sahu; Deepchandra Srivastava; Jay Dave; Navaneeth Meena Thamban; Sreenivas Gaddamidi; Lokesh Sahu; Mayank Kumar; Vikram Singh; et al. (Atmospheric Environment, 2023)

Potential Microbial Consortium Mitigates Drought Stress in Tomato (Solanum lycopersicum L.) Plant by Up-regulating Stress-Responsive Genes and Improving Fruit Yield and Soil Properties - Ram Krishna; Durgesh Kumar Jaiswal; Waquar Akhter Ansari; Saurabh Singh; P. S. Soumia; Achuit Kumar Singh; Babita Kumari; Major Singh; Jay Prakash Verma (Journal of Soil Science and Plant Nutrition, 2022)

Enrichment Factor and Chemical Composition of Size Separated Airborne Particulate Matter of Singrauli Coalfield, India - Akhilesh Kumar Yadav; Sunil Kumar Sahoo; Aditi Chakrabarty Patra; Virender Kumar Thakur; Jay Singh Dubey; Sarjan Singh; Pradyumna Lenka; Vivekanand Jha; Aerattukkara Vinod Kumar; Saba Shirin; Aarif Jamal (Aerosol Science and Engineering, 2022)

Partial replacement of cement with induction furnace dust for enhancing concrete properties with and without Aspergillus niger fungus: a green building approach - Jay Kumar; Amanpreet Kaur Sodhi; Neeraj Bhanot (Environmental Science and Pollution Research, 2022)

Isolation and functional characterization of a fungal plant symbiont Nigrospora sphaerica, associated to Euphorbia hirta L. - Veer Singh Gautam; Jay Hind Nishad; Puja Kumari; Arti Singh; Satish Kumar Verma; Vijay Kumar Sharma; Jitendra Kumar; Ravindra Nath Kharwar (Indian Phytopathology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Determination and assessment of elemental concentration in the atmospheric particulate matter: a comprehensive review - Jay Singh Rajput; Manoj Kumar Trivedi (Environmental Monitoring and Assessment, 2022)

Phenolic and flavonoid contents and antioxidant activity of an endophytic fungus Nigrospora sphaerica (EHL2), inhabiting the medicinal plant Euphorbia hirta (dudhi) L. - Veer Singh Gautam; Arti Singh; Puja Kumari; Jay Hind Nishad; Jitendra Kumar; Monika Yadav; Rajnish Bharti; Priyanka Prajapati; Ravindra Nath Kharwar (Archives of Microbiology, 2022)

Simultaneous exposure to electromagnetic field from mobile phone and unimpeded fructose drinking during pre-, peri-, and post-pubertal stages perturbs the hypothalamic and hepatic regulation of energy homeostasis by early adulthood: experimental evidence - Ruchi Tripathi; Sanjay Kumar Banerjee; Jay Prakash Nirala; Rajani Mathur (Environmental Science and Pollution Research, 2022)

Overexpression of AtDREB1 and BcZAT12 genes confers drought tolerance by reducing oxidative stress in double transgenic tomato (Solanum lycopersicum L.) - Ram Krishna; Waquar Akhter Ansari; Durgesh Kumar Jaiswal; Achuit Kumar Singh; Ram Prasad; Jay Prakash Verma; Major Singh (Plant Cell Reports, 2021)

Landslide probability mapping by considering fuzzy numerical risk factor (FNRF) and landscape change for road corridor of Uttarakhand, India - Ujjwal Sur; Prafull Singh; Praveen Kumar Rai; Jay Krishna Thakur (Environment, Development and Sustainability, 2021)

Bioactive potential evaluation and purification of compounds from an endophytic fungus Diaporthe longicolla, a resident of Saraca asoca (Roxb.) Willd. - Jay Hind Nishad; Arti Singh; Veer Singh Gautam; Puja Kumari; Jitendra Kumar; Monika Yadav; Ravindra Nath Kharwar (Archives of Microbiology, 2021)

Comparative RNA-Seq analysis of the root revealed transcriptional regulation system for aluminum tolerance in contrasting indica rice of North East India - Jay Prakash Awasthi; Kazutaka Kusunoki; Bedabrata Saha; Yuriko Kobayashi; Hiroyuki Koyama; Sanjib Kumar Panda (Protoplasma, 2021)

Exogenous trehalose ameliorates methyl viologen induced oxidative stress through regulation of stomatal pore opening and glutathione metabolism in tomato seedlings - Pankaj Borgohain; Bhaben Chowardhara; Bedabrata Saha; Jay Prakash Awasthi; Preetom Regon; Smita Sahoo; Sanjib Kumar Panda (Vegetos, 2020)

Analysis of association between various fertility indicators and production traits in Mehsana buffaloes - Rishit Navinchandra Sathwara; Jay Prakash Gupta; Jagdish Devjibhai Chaudhari; Girish Ambalal Parmar; Bhavesh Manubhai Prajapati; Amit Kumar Srivastava; Hareshkumar Dashrathlal Chauhan; Pravinbhai Ambalal Patel; Mukeshbhai Natulal Prajapati (Tropical Animal Health and Production, 2020)

Molecular Investigation of the Status of Ticks on Infected Cattle for Coxiella burnetii in India - Pankaj Dhaka; Satya Veer Singh Malik; Jay Prakash Yadav; Srikant Ghosh; Manesh Kumar; Sukhadeo B. Barbuddhe; Deepak B. Rawool (Acta Parasitologica, 2020)

Differential oxidative stress responses in Brassica juncea (L.) Czern and Coss cultivars induced by cadmium at germination and early seedling stage - Bhaben Chowardhara; Pankaj Borgohain; Bedabrata Saha; Jay Prakash Awasthi; Sanjib Kumar Panda (Acta Physiologiae Plantarum, 2020)

Redox status and oxalate exudation determines the differential tolerance of two contrasting varieties of ‘Assam tea’ [Camelia sinensis (L.) O. Kuntz] in response to aluminum toxicity - Sanjenbam Sanjibia Devi; Bedabrata Saha; Jay Prakash Awasthi; Preetom Regon; Sanjib Kumar Panda (Horticulture, Environment, and Biotechnology, 2020)

Effect of mobile phone radiation on oxidative stress, inflammatory response, and contextual fear memory in Wistar rat - Kumari Vandana Singh; Rohit Gautam; Ramovtar Meena; Jay Prakash Nirala; Sushil Kumar Jha; Paulraj Rajamani (Environmental Science and Pollution Research, 2020)

Management of De Novo Carotid Stenosis and Postintervention Restenosis—Carotid Endarterectomy Versus Carotid Artery Stenting—a Review of Literature - Runqi Wangqin; Paul R. Krafft; Keaton Piper; Jay Kumar; Kaya Xu; Maxim Mokin; Zeguang Ren (Translational Stroke Research, 2019)

Quantification of Fundamental Frequencies of 3D Basins and Structures and Site–City Interaction Effects on Responses of Structures - Neeraj Kumar; Jay Prakash Narayan (Pure and Applied Geophysics, 2019)

Impact of semen-derived amyloid (SEVI) on sperm viability and motility: its implication in male reproductive fitness - Vijay Kumar; Pradeep G. Kumar; Jay Kant Yadav (European Biophysics Journal, 2019)

Assessment of particulate matter, metals of toxicological concentration, and health risk around a mining area, Odisha, India - Akhilesh Kumar Yadav; Sunil Kumar Sahoo; Jay Singh Dubey; Aerattukkara Vinod Kumar; Govind Pandey; Raj Mangal Tripathi (Air Quality, Atmosphere & Health, 2019)

Physiological introspection into differential drought tolerance in rice cultivars of North East India - Smita Sahoo; Bedabrata Saha; Jay Prakash Awasthi; Takhellambam Omisun; Pankaj Borgohain; Safiqul Hussain; Jogeswar Panigrahi; Sanjib Kumar Panda (Acta Physiologiae Plantarum, 2019)

Development of Microbial Consortia for Growth Attributes and Protein Content in Micropropagated Bacopa monnieri (L.) - Jay Prakash Verma; Kavindra Nath Tiwari; Janardan Yadav; Awadhesh Kumar Mishra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Screening of bacterial strains for developing effective pesticide-tolerant plant growth-promoting microbial consortia from rhizosphere soils of vegetable fields of eastern Uttar Pradesh, India - Jay Prakash Verma; Durgesh Kumar Jaiswal; Punkaj Kumar Maurya (Energy, Ecology and Environment, 2016)

Assessing Potential Conservation and Restoration Areas of Freshwater Fish Fauna in the Indian River Basins - Jay P. Bhatt; Kumar Manish; Rajender Mehta; Maharaj K. Pandit (Environmental Management, 2016)

Pesticide relevance and their microbial degradation: a-state-of-art - Jay Prakash Verma; Durgesh Kumar Jaiswal; R. Sagar (Reviews in Environmental Science and Bio/Technology, 2014)

Study of combined effects of sediment rheology and basement focusing in an unbounded viscoelastic medium using P-SV-wave finite-difference modelling - Jay P. Narayan; Vinay Kumar (Acta Geophysica, 2014)

Deciphering the Roles of Trehalose and Hsp104 in the Inhibition of Aggregation of Mutant Huntingtin in a Yeast Model of Huntington’s Disease - Rajeev Kumar Chaudhary; Jay Kardani; Kuljit Singh; Ruchira Banerjee; Ipsita Roy (NeuroMolecular Medicine, 2014)

Computation of ground motion amplification in Kolkata megacity (India) using finite-difference method for seismic microzonation - Amit Shiuly; Vinay Kumar; Jay P. Narayan (Acta Geophysica, 2014)

Outcomes from a Postgraduate Biomedical Technology Innovation Training Program: The First 12 Years of Stanford Biodesign - Todd J. Brinton; Christine Q. Kurihara; David B. Camarillo; Jan B. Pietzsch; Julian Gorodsky; Stefanos A. Zenios; Rajiv Doshi; Christopher Shen; Uday N. Kumar; Anurag Mairal; Jay Watkins; Richard L. Popp; et al. (Annals of Biomedical Engineering, 2013)

Delineating groundwater potential zones in a hard-rock terrain using geospatial tool - Prafull Singh; Jay Krishana Thakur; Suyash Kumar (Hydrological Sciences Journal, 2013)

Increase in growth, productivity and nutritional status of rice (Oryza sativa L. cv. Basmati) and enrichment in soil fertility applied with an organic matrix entrapped urea - Manoj Kumar; Kuldeep Bauddh; Manish Sainger; Poonam Ahlawat Sainger; Jay Shankar Singh; Rana Pratap Singh (Journal of Crop Science and Biotechnology, 2012)

Study of effects of focal depth on the characteristics of Rayleigh waves using finite difference method - Jay P. Narayan; Sanjay Kumar (Acta Geophysica, 2010)

Effects of soil layering on the characteristics of basin-edge induced surface waves - Jay Prakash Narayan; Sanjay Kumar (Acta Geophysica, 2009)

Absorbing boundary conditions in a fourth-order accurate SH-wave staggered grid finite difference algorithm - Sanjay Kumar; Jay Prakash Narayan (Acta Geophysica, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)